Legal Analysis of Restorative Justice Practices in Resolving Child Crime Cases in Indonesia - Haspada, Deny (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
This research examines the practice of restorative justice in resolving child crime cases in Indonesia and its legal implications. The main focus is analyzing the existing legal framework and the effectiveness of implementing restorative justice in dealing with crimes involving children. The research method used is a qualitative approach with data collection techniques through in-depth interviews and analysis of legal documents. The research results show that restorative justice has a positive impact on the rehabilitation of child perpetrators and the recovery of victims. However, there are challenges in implementation, including a lack of understanding and training among law enforcement. This study found that existing regulations do not fully support restorative justice practices. Additionally, this research compares implementation in Indonesia with other countries, demonstrating the need for legal reform. The conclusion of this research is that there is great potential for restorative justice to be implemented more widely by improving regulations and increasing the capacity of law enforcement. This research contributes to the development of a more comprehensive and effective legal framework for handling child crimes in Indonesia.